KONEKTIVITAS STRUKTUR VEGETASI MANGROVE DENGAN KEASAMAN DAN BAHAN ORGANIK TOTAL PADA SEDIMEN DI KECAMATAN WONOMULYO KABUPATEN POLEWALI MANDAR - Saru, Amran; Amri, Khairul; Mardi, Mardi (Jurnal Ilmu Kelautan SPERMONDE, 2017)
Mangrove forest ecosystem is one of coastal ecosystem having significant roles as habitat for diverse organisms, as barrier ofseawater intrusion, sediment trap, protection to the shore from abrasion and as nutrient supplier in form of detritus to othercoastal ecosystems i.e. seagrass beds and coral reefs. However, mangrove has experienced degradation caused by natural andanthropogenic factors. One effort to recover the mangrove’s function is by rehabilitating this ecosystem through controllingits total organic matter and the soil acidity (pH). Therefore, it is urgent to conduct a study in order to know the relationshipbetween mangrove growth and the total organic matter and pH. The study was conducted May 2014. The study area was locatedin Mampie, Wonomulyo Sub-District, Polewali Mandar Regency. The benefit gained from this study was giving information ondissolved organic matter related to the mangrove rehabilitation. Method used was field survey by determining three observationstations with different environmental condition. Data were presented as tables and pictures. Results of this study indicated thatincreasing of mangrove density and coverage was followed by the increasing of total organic matter percentage within sedimentat station II. Whereas, the higher the acidity, the lower the content of the total organic matter within sediment was found inStation I. In contrast, the organic matter within sediment was high when the acidity value decrease was observed at Station III.Keywords: Vegetation structure, mangrove, environmental factors, Dissolved Organic Matter, pH.